One step cyclocondensation of (thio) barbituric acid with chalcones in glacial acetic acid and phosphorous pentoxide, Part-II (Bangladesh Journal of Scientific and Industrial Research, 2017)
A number of new 5, 7-diaryl-1,5-dihydro (or 1, 2, 3, 5-tetrahydro)- pyrano [2, 3-d] pyrimidin-2, 4-diones (or 2-thioxo-4-ones) (3a-g) have  been synthesized in one-step by cyclocondensation of barbituric acid or thiobarbituric acid (1) with arylideneacetophenones (2a-d), in glacial  acetic acid in the presence of phosphorous pentoxide. The structures of the compounds 3a-g have been determined by UV, IR, 1H NMR, 13C  NMR, mass spectral data and elemental analyses. The compounds 3a-g do not seem to be available in the literature.Bangladesh J. Sci. Ind. Res. 52(2), 115-124, 2017